2022
DOI: 10.3390/w14050816
|View full text |Cite
|
Sign up to set email alerts
|

Modified Hazelnut Shells as a Novel Adsorbent for the Removal of Nitrate from Wastewater

Abstract: The aim of the study was to prepare a novel adsorbent by chemical modification of hazelnut shells and evaluate its potential for the nitrate removal from model solutions and real wastewater. The characterization of the novel adsorbent, i.e., modified hazelnut shell (MHS) was performed. The adsorbent characterization included the analysis of elemental composition and the surface characteristics analysis by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The adsorption expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The effectiveness of the HNTs and HNTs-CTAB in the removal of nitrate has been examined using batch adsorption modes. 49,50 A determined quantity of each adsorbent (10 mg) in tubes containing 10 ml of a NO 3 solution (100 mg/L) was kept with a speed of 200 rpm at initial pH solution of about 5.4 at room temperature.…”
Section: Batch-adsorption Experimentsmentioning
confidence: 99%
“…The effectiveness of the HNTs and HNTs-CTAB in the removal of nitrate has been examined using batch adsorption modes. 49,50 A determined quantity of each adsorbent (10 mg) in tubes containing 10 ml of a NO 3 solution (100 mg/L) was kept with a speed of 200 rpm at initial pH solution of about 5.4 at room temperature.…”
Section: Batch-adsorption Experimentsmentioning
confidence: 99%
“…Several chemical activation agents have been used to chemically activate the surface of agricultural waste, such as dimethylamine/epichlorohydrin grafted onto the surface of several by-products (sugarcane bagasse, hazelnuts, and rice shells). This chemical activation improved the ability of these by-products to adsorb NO 3 − which expected q e of 55.6 mg/g in the case of rice peel [54][55][56]. Other chemicals with amino functions, such as cetyltrimethylammonium bromide [53], polyethyleneimine [57], N-(3-chloro-2hydroxypropyl) trimethylammonium chloride (CHMAC) [55], and 3-aminopropyltriethoxy silane (APTES) [58] have also been commonly used to improve the adsorption of NO 3 − anions.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, in general, agro-resources are increasingly used in water treatment to reduce the environmental impact of many activities, such as fabric dyeing [41][42][43][44], molecular detection of chemical elements [45,46], and pollutant removal. In this regard, several studies have reported the use of ago-wastes (raw and modified) as adsorbents for several pollutants such as dyes [47,48], heavy metals [49][50][51], and NO 3 − /PO 4 3− anions [52][53][54][55][56]. The natural raw materials mentioned above adsorb pollutants but inefficiently with low adsorption capacity (qe).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that the low anion exchange capacity of soils frequently limits the removal performance of nitrate. As a result, carbon additions such as woodchips, sawdust, crop residues and biochar have been suggested for nitrate removal [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%